On the ‘commemorative’ use of the Italian Indicativo Imperfetto - Mazzoleni, Marco (Cuadernos de Filología Italiana, 2012)
There is a particular use of the Italian imperfect indicative that appears to suggest that the state of affairs presented by the speaker is not simply situated in the past – i.e. happened at a time chronologically previous to the utterance – but also something that is now finally and irrevocably closed and finished, i.e. a state of affairs that no longer exists. If in Italian one says «s/he was (era) a fine person», this automatically suggests that the person spoken of has passed on and is no longer with us, or alternatively that his/her habitual behaviour has taken a decisive turn for the worse. This research intends to illustrate briefly this use of the imperfect in a number of discourse and textual genres in modern and contemporary Italian, alongside with the use of the simple past (perfetto semplice) of essere, typified in Manzoni’s unforgettable «Ei fu» («he has passed» in some translations of his poem The Fifth of May), a use now typical of the bureaucratic language referred to ironically in the title of Pirandello’s Il fu Mattia Pascal (The late Mattia Pascal).
Keywords: Imperfect indicative; Simple past; Commemorative Texts / Speeches; Aspect.